Vascular risk factors, cognitve decline, and dementia - Duron, E (Dove Medical Press, 2008)
Dementia is one of the most important neurological disorders in the elderly. Aging is associated with a large increase in the prevalence and incidence of degenerative (Alzheimer’s disease) and vascular dementia, leading to a devastating loss of autonomy. In view of the increasing longevity of populations worldwide, prevention of dementia has turned into a major public health challenge. In the past decade, several vascular risk factors have been found to be associated with vascular dementia but also Alzheimer’s disease. Some longitudinal studies, have found significant associations between hypertension, diabetus mellitus, and metabolic syndrome, assessed at middle age, and dementia. Studies assessing the link between hypercholesterolemia, atrial fibrillation, smoking, and dementia have given more conflicting results. Furthermore, some studies have highlighted the possible protective effect of antihypertensive therapy on cognition and some trials are evaluating the effects of statins and treatments for insulin resistance. Vascular risk factors and their treatments are a promising avenue of research for prevention of dementia, and further long-term, placebo-controlled, randomized studies, need to be performed.